Depressive Disorders of Affective Register in Students with Cardiovascular Disease - VashkiteІ. D. (Psychiatry, Neurology and Medical Psychology, 2015)
We consider the causes, methods of diagnosis and treatment of depressive disorders of aff ective registers in high schools students with cardiovascular disease. The author indicates the number of diagnostic examinations and preliminary results of emotional students. The author makes recommendations for diagnosis and treatment of depression in primary health level.